2022
DOI: 10.3389/fendo.2021.800376
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID19 in Patients With Osteogenesis Imperfecta: A Retrospective Multicenter Study in Saudi Arabia

Abstract: BackgroundAlthough genetic diseases are rare, children with such conditions who get infected with COVID-19 tend to have a severe illness requiring hospitalization. Osteogenesis imperfecta (OI) is a rare genetic disorder of collagen resulting in fractures and skeletal deformities. Kyphoscoliosis, restrictive lung disease, and pneumonia worsen the prognosis of patients with OI. The use of bisphosphonate improves bone mineral density (BMD) and reduces fractures in OI. There is no literature describing the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…There is a need for countries to address the unmet need for investment in prevention of illness for those with rare diseases via clinical research and development activities ( 29 ). It is reassuring however that evidence to date shows that COVID-19 infection does not have a particularly adverse effect on those with OI ( 30 ). During the pandemic, the BBS provided online COVID-19 information to its members, with the majority of respondents finding this very helpful.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for countries to address the unmet need for investment in prevention of illness for those with rare diseases via clinical research and development activities ( 29 ). It is reassuring however that evidence to date shows that COVID-19 infection does not have a particularly adverse effect on those with OI ( 30 ). During the pandemic, the BBS provided online COVID-19 information to its members, with the majority of respondents finding this very helpful.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, patients with COL1A1+COL1A2 gene mutations have shown various forms of cardiovascular pathology, particularly regurgitation of the heart valves, attributed to poor collagen [ 119 ]. Interestingly, a small study examining pediatric OI patients found that they had no difference in outcome after COVID-19 infection [ 120 ]. Moreover, two therapies used for OI, mesenchymal stem cells and decidua stromal cells were used to treat SARS-CoV-2 coronavirus-induced disease [ 121 ] as an anti-inflammatory treatment to reduce COVID-induced cytokine storm.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Alshukairi et al, children with osteogenesis imperfecta and COVID-19 exhibited a mild course of the disease and recovered without complications [110]. Children with metabolic bone disease or a skeletal dysplasia that affect chest wall structure and respiratory sufficiency may be at increased risk of COVID-19 complications [111].…”
Section: Metabolic Bone Diseasementioning
confidence: 99%